Native monocots of the Corredor Biológico Chichinautzin - Pulido-Esparza, Valeria Angélica; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2009)
The Corredor Biológico Chichinautzin is a natural protected area with an extension of 65,901 ha. Within its boundaries seven vegetation types are represented in an altitudinal range from 1200 to 3400 m. Revision of herbarium collections and bibliography, and field specimens collections, let us to obtain the inventory of native monocots species present in the area. The inventory comprises 359 species, 132 genera and 25 families. Orchidaceae and Bromeliaceae stand out by their endemism level. In the area grow six exclusive species.